Subak Padanggalak Development Strategy as Tourism Attraction in Denpasar City Bali - I Ketut Surya Diarta; I Made Sarjana (Media Konservasi, 2018)
The development of subak as tourist attraction will be inline within Bali cultural tourism development, since subak and tourism in Bali are both are Balinese culturally basis. This is an effort to maintain the sustainability of subak while controlling the paddy field conversion and supporting environmental sustainability. However, the absence of subak strategy as tourist attraction becomes a problem. This paper analyzes the internal and external environmental factors that influence Subak Padanggalak, Denpasar City, Bali as tourism attraction and designing the subak strategy as tourism attraction in urban area. To do so, it will be analyzed using SWOT and Quantitative Strategic Planning Matrix (QSPM). The I-E matrix analysis falls into cell V, namely using maintain subak as tourism attraction dan pushing market penetration and product development. SWOT analysis produces four alternative strategies, namely: (a) S-O strategy (expansion of tourist markets, provision of subak tourism facilities), (b) S-T strategy (stressing agricultural activities and rituals as tourist attractions, tourism activities based on subak norms and rules, involving subak members in subak tourism activities), (c) W-O strategy (subak is more involved in developing tourism attraction and cooperating with government), and (d) W-T strategy (strict rules for controlling land conversion, limiting the coming of external labor working in subak, and adequate facilities to empower farmers and foster public appreciation of subak). Priority analysis of the subak strategy successively starts from the development of tourist attraction based on agricultural activities and rituals in subak through cooperation with the government and entrepreneurs to empower farmers through providing additional sources of income from tourism activities. To ensure the sustainability of subak, it is necessary to have strict rules to control the conversion of agricultural land functions, and limit the external workforce to subak. The strategy must be is in line with subak norms and rules to achieve sustainability of subak-based urban tourism attraction. Keywords: attraction, Denpasar, development strategy, subak, tourism